TINJAUAN HUKUM ATAS KEDUDUKAN KUASA HUKUM PADA PENGADILAN PAJAK - Yadhy Cahyady (Politeknik Keuangan Negara STAN, 2019)
ABSTRACTTax Court is a part of the Administrative Court under the judicial power of the Supreme Court of Indonesia that exercises judicial power for tax payers or tax beares seeking justice for tax disputes. The respective parties in disputes can be represented by one or more legal proxies by special power of attorney. To become a legal proxy, a person must fulfill the requirements as stipulated by Minister of Finance and prossess a license from the Chairman of Tax Court. Furthermore, if the legal proxy is an advocate, he/she must fulfill the requirements as stated in Law Number 14 Year 2002 Concerning Tax Court.